The Gender Digital Divide in Developing Countries - Amy Antonio; David Tuffley (Future Internet, 2014)
Empirical studies clearly show that women in the developing world have significantly lower technology participation rates than men; a result of entrenched socio-cultural attitudes about the role of women in society. However, as studies are beginning to show, when those women are able to engage with Internet technology, a wide range of personal, family and community benefits become possible. The key to these benefits is on-line education, the access to which sets up a positive feedback loop. This review gives an overview of the digital divide, before focusing specifically on the challenges women in developing countries face in accessing the Internet. Current gender disparities in Internet use will be outlined and the barriers that potentially hinder women’s access and participation in the online world will be considered. We will then look at the potential opportunities for women’s participation in a global digital society along with a consideration of current initiatives that have been developed to mitigate gender inequity in developing countries. We will also consider a promising avenue for future research.